Gender differences in judging intentionality: How the reaction time and sensitivity to provocation moderates this relationship. (1st October 2020) - Zajenkowska, Anna; Rajchert, Joanna; Lawrence, Claire
Abstract: One of the main factors that triggers aggression in both men and women is the perceived intentionality of the harm doer. The current study focuses on non-verbal behavior, namely the speed at which individuals (N = 151, females = 90) make decisions of intent. Specifically, it investigates whether there is any relationship between participants' gender and their intentionality judgments for hostile, accidental and ambiguous scenes moderated by participants' individual differences in sensitivity to provocation and the time participants take to make these judgments. Results showed that men and women differ when they have low sensitivity to provocations (SP) and faster reaction times. Compared to men, women ascribe more intentionality, in case of ambiguous scenes depicting female actors and all hostile scenes. Also there were gender differences in case of participants who were high in SP. The faster they made decisions, the more likely they were to make attributions of hostile intent (male participants) or low intent (female participants).